2022
DOI: 10.3389/fpls.2022.951003
|View full text |Cite
|
Sign up to set email alerts
|

Combined de novo transcriptomic and physiological analyses reveal RyALS3-mediated aluminum tolerance in Rhododendron yunnanense Franch

Abstract: Rhododendron (Ericaceae) not only has ornamental value, but also has great medicinal and edible values. Many Rhododendron species are native to acid soils where aluminum (Al) toxicity limits plant productivity and species distribution. However, it remains unknown how Rhododendron adapts to acid soils. Here, we investigated the physiological and molecular mechanisms of Al tolerance in Rhododendron yunnanense Franch. We found that the shoots of R. yunnanense Franch did not accumulate Al after exposure of seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Al 3+ can be compartmentalized into vacuoles to reduce cytoplasmic Al 3+ content through a mechanism mainly controlled by the ABC transporter ALS. RyALS3 is located on the vacuole membrane in Rhododendron yunnanense and mediates Al partitioning into the vacuole (Xu, Lei, et al., 2022). AtALS1 is also located in the tonoplast and is responsible for transporting Al from the cytoplasm to vacuoles under Al toxicity (Larsen et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al 3+ can be compartmentalized into vacuoles to reduce cytoplasmic Al 3+ content through a mechanism mainly controlled by the ABC transporter ALS. RyALS3 is located on the vacuole membrane in Rhododendron yunnanense and mediates Al partitioning into the vacuole (Xu, Lei, et al., 2022). AtALS1 is also located in the tonoplast and is responsible for transporting Al from the cytoplasm to vacuoles under Al toxicity (Larsen et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ALS3 participates in the Al tolerance mechanism of plants through interaction with cinnamyl alcohol deaminase (CAD) (Wu et al., 2019). RyALS3 also transports Al from the cytoplasm into vacuoles and mediates the fixation of Al in roots, thereby improving Al tolerance of plants (Xu, Lei, et al., 2022). Previous studies have also shown that sensitive to proton rhizotoxicity (STOP), the core transcription factor responding to AlCl 3 stress enhances compartmentalization of Al in vacuoles by regulating the expression of ALS3 .…”
Section: Introductionmentioning
confidence: 99%
“…Each product was ligated into the binary vector (pCAMBIA1300-35S::GFP) to produce a Pro35S::RsHsf::GFP construct, which was then transformed into Agrobacterium tumefaciens strain EHA105. The transformed A. tumefaciens was used to infiltrate the leaves of 4-week-old tobacco plants [58]. At 48-72 h after infiltration, GFP signals were observed using Nikon Eclipse Ni-U microscope (Nikon, Tokyo, Japan).…”
Section: Subcellular Localization Analysesmentioning
confidence: 99%
“…In China, rhododendrons are mainly distributed in the southwestern region, in which soil acidification is severe [ 38 ]. Rhododendrons can grow well in acidic soil with high Al concentrations, implying they may have evolved complex mechanisms that enable them to effectively cope with Al stress [ 39 ]. Due to the different genetic backgrounds, the morphology, traditional use, phytochemistry and pharmacology of different varieties of rhododendrons are very different, which may lead to the great differences in their physiology and biochemistry [ 40 ].…”
Section: Introductionmentioning
confidence: 99%